Multi-stage serpentinization of ultramafic rocks in the Manlay Ophiolite, southern Mongolia (Mongolian Geoscientist, 2021)
Serpentinization of ultramafic rocks in ophiolites is key to understanding the global cycle of elements and changes in the physical properties of lithospheric mantle. Mongolia, a central part of the Central Asian Orogenic Belt (CAOB), contains numerous ophiolite complexes, but the metamorphism of ultramafic rocks in these ophiolites has been little studied. Here we present the results of our study of the serpentinization of an ultramafic body in the Manlay Ophiolite, southern Mongolia. The ultramafic rocks were completely serpentinized, and no relics of olivine or orthopyroxene were found. The composition of Cr-spinels [Mg# = Mg/(Mg + Fe2+) = 0.54 and Cr# = Cr/(Cr + Al) = 0.56] and the bulk rock chemistry (Mg/Si = 1.21–1.24 and Al/Si < 0.018) of the serpentinites indicate their origin from a fore-arc setting. Lizardite occurs in the cores and rims of mesh texture (Mg# = 0.97) and chrysotile is found in various occurrences, including in bastite (Mg# = 0.95), mesh cores (Mg# = 0.92), mesh rims (Mg# = 0.96), and later-stage large veins (Mg# = 0.94). The presence of lizardite and chrysotile and the absence of antigorite suggests low-temperature serpentinization (